Motivations and expectations of young graduates of technical education: continuity or not configure studies uncertain trajectories - Ferreira, Danilo José; Raitz, Tânia Regina (Seven Editora, 2023)
This article presents analytical results of an investigation that aimed to analyze the motivations and expectations of young graduates of the Agricultural Technical Education of Santa Catarina, the IFCCamboriú (Federal Institute of Santa Catarina). The concept of rural student-worker was significant to understand it as a social being that contributes to the growth of society and the agricultural sector through its work. The research is a qualitative approach to its development and data collection using bibliographical research, questionnaire, and individual interviews with 24 (twenty-four) former students of the institution. The developed theoretical and methodological assumptions are based on the work category (ontological perspective) and youth from a historical and socio-cultural perspective. The results confirm the thesis that the Technical Course in Agriculture in the study group, are not reaching their goals in training for work in the specific branch of Agriculture, despite a conducive and attractive setting for graduates in entering the agribusiness labor market and continued studies in this area. Educational centers need to work more extensively on the possibilities and stimulating labor camps, developing entrepreneurship. Thus it is possible to strengthen the region in which you install the course. DOI: https://doi.org/10.56238/devopinterscie-040